The Role Of Peer Education To Prevent Early Marriage Among Adolescents In Indonesia - Theresia Angelina Duma Octavia Pardede (International Journal of Health Engineering and Technology, 2026)
The high rate of early marriage in Indonesia is a serious challenge that has an impact on the risks of reproductive health, education, and social welfare of adolescents. Peer education has emerged as a promising intervention strategy, but the effectiveness and determinants of its success of various community service programs in Indonesia require a comprehensive synthesis. This study aims to evaluate the effectiveness of various peer education methods, identify determinants of success, and analyze the challenges of implementing public health strategies in reducing the rate of early marriage in Indonesia. A systematic review was conducted on 18 research articles (consisting of community service actions and quantitative research) published between 2019 and 2026. The analysis was carried out by grouping interventions based on methods, objectives, and outputs achieved, then synthesized to answer the urgency of peer intervention in Indonesia. The results of the analysis showed that the peer education method was consistently able to increase knowledge and change adolescents' attitudes to be more rational (p<0.05). Determinants of success include the convenience of horizontal communication between peers, the use of creative educational media (such as Monopoly Genres and digital platforms), and the integration of programs with formal structures at the village or school level (such as PIK-R and Village Decree policies). However, implementation is still hampered by traditional cultural norms, social pressures, and a lack of post-program sustainability support, as well as structural challenges related to family economics in rural areas. It can be concluded that peer education is a very effective strategy to cut communication barriers on sensitive adolescent reproductive health issues. The sustainability of the program is highly dependent on cross-sectoral collaboration between health offices, village officials, and youth cadres. A more holistic health promotion model is needed by aligning reproductive education, legal protection advocacy, and family economic empowerment to have a systemic and long-term impact.